The ASC Division on Women and Crime From 30 Years Out. (October 2014) - Rasche, Christine E.
The Division on Women and Crime (DWC) of the American Society of Criminology (ASC) is celebrating its 30th Anniversary in 2014. Anniversaries are good times to reflect on where we have come from and where we are going. This article traces the history and origins of the DWC from its inception in the 1970s, through its struggles in the 1980s to win recognition within the ASC, to its current status today as one of the largest and most vibrant divisions within the ASC. The discussion includes the DWC's development within a traditionally male-dominated profession and parallel to the emergence of the women's movement in the United States, along with an analysis of specific strategies employed by the DWC which helped to make it successful within that context.